Kinetics of molybdenum reduction to molybdenum blue by Bacillus sp. strain A.rzi - Othman, Ahmad Razi; Abu Bakar, Nurlizah; Halmi, Mohd Izuan Effendi; Wan Johari, Wan Lutfi; Ahmad, Siti Aqlima; Jirangon, Hussain; Syed, Mohd Arif; Abd. Shukor, Mohd. Yunus (Hindawi Publishing Corporation, 2013)
Molybdenum is very toxic to agricultural animals. Mo-reducing bacterium can be used to immobilize soluble molybdenum to insoluble forms, reducing its toxicity in the process. In this work the isolation of a novel molybdate-reducing Gram positive bacterium tentatively identified as Bacillus sp. strain A.rzi from a metal-contaminated soil is reported. The cellular reduction of molybdate to molybdenum blue occurred optimally at 4 mM phosphate, using 1% (w/v) glucose, 50 mM molybdate, between 28 and 30°C and at pH 7.3. The spectrum of the Mo-blue product showed a maximum peak at 865 nm and a shoulder at 700 nm. Inhibitors of bacterial electron transport system (ETS) such as rotenone, sodium azide, antimycin A, and potassium cyanide could not inhibit the molybdenum-reducing activity. At 0.1 mM, mercury, copper, cadmium, arsenic, lead, chromium, cobalt, and zinc showed strong inhibition on molybdate reduction by crude enzyme. The best model that fitted the experimental data well was Luong followed by Haldane and Monod. The calculated value for Luong's constants pmax, Ks, Sm, and n was 5.88 mole Mo-blue hr-1, 70.36 mM, 108.22 mM, and 0.74, respectively. The characteristics of this bacterium make it an ideal tool for bioremediation of molybdenum pollution.